SOFTWARE SIMULASI UJIAN NASIONAL BERBASIS MOBILEAPPLICATION MENGGUNAKAN BAHASA PEMROGRAMANJAVA 2 MICRO EDITION (J2ME) - Adhi Wicaksono, Nova Suparmanto, dan Rahmat Hidayat (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
“Software Simulasi Ujian Nasional Berbasis Mobile Application MenggunakanBahasa Pemrograman Java 2 Micro Edition (J2ME)” is a solution and innovation inaddressing the graduation rate of students is getting lower and to increase studentinterest in learning so as to make preparation for the national exam is more mature andis expected to achieve satisfactory results with high rates of graduation. The goal inmaking this software are 1) Can design and create a